Cannabidiol and cannabis-inspired terpene blends have acute prosocial effects in the BTBR mouse model of autism spectrum disorder - Staben, Jenika; Koch, Megan; Reid, Keelee; Muckerheide, Jessica; Gilman, Lauren; McGuinness, Finn; Kiesser, Sarina; Oswald, Iain W. H.; Koby, Kevin A.; Martin, Thomas J.; Kaplan, Joshua S. (Frontiers in Neuroscience, 2023)
Introduction Cannabidiol (CBD) is a non-intoxicating phytocannabinoid with increasing popularity due to its purported therapeutic efficacy for numerous off-label conditions including anxiety and autism spectrum disorder (ASD). Those with ASD are commonly deficient in endogenous cannabinoid signaling and GABAergic tone. CBD has a complex pharmacodynamic profile that includes enhancing GABA and endocannabinoid signaling. Thus, there is mechanistic justification for investigating CBD’s potential to improve social interaction and related symptoms in ASD. Recent clinical trials in children with ASD support CBD’s beneficial effects in numerous comorbid symptoms, but its impact on social behavior is understudied. Methods Here, we tested the prosocial and general anxiolytic efficacy of a commercially available CBD-rich broad spectrum hemp oil delivered by repeated puff vaporization and consumed via passive inhalation in the female cohort of the BTBR strain, a common inbred mouse line for preclinical assessment of ASD-like behaviors. Results We observed that CBD enhanced prosocial behaviors using the 3-Chamber Test with a different vapor dose-response relationship between prosocial behavior and anxiety-related behavior on the elevated plus maze. We also identified that inhalation of a vaporized terpene blend from the popular OG Kush cannabis strain increased prosocial behavior independently of CBD and acted together with CBD to promote a robust prosocial effect. We observed similar prosocial effects with two additional cannabis terpene blends from the Do-Si-Dos and Blue Dream strains, and further reveal that these prosocial benefits rely on the combination of multiple terpenes that comprise the blends. Discussion Our results illustrate the added benefit of cannabis terpene blends for CBD-based treatment of ASD.